Sei sulla pagina 1di 10

ECE/CpE 307S ADVANCED ENGG MATH for ECE/CpE COLLEGE OF ENGINEERING COLEGIO SAN AGUSTIN

Topic: Laplace Transform Prepared by: Engr. Vicente Y. Buenconsejo, Jr., PECE, MT

Pierre Simon Marquis De Laplace (1749-1827), great French mathematician develop the theory of potential and contributions to celestial mechanics, astronomy in general, special functions, and probability theory. Napoleon Bonaparte was his student for a year.

3 Main Steps

1. The given hard problem is transformed into a simple equation called subsidiary equation.

2. The subsidiary equation is solved by purely algebraic manipulations.

3. The solution of the subsidiary equation is transformed back to obtain the solution of the given problem.

These process is made easier by tables of functions and their transforms, whose role is similar to that of integral tables of calculus. The switching from operations of calculus to algebraic operations on transforms is called OPERATIONAL CALCULUS. For engineers, Laplace transform method is practically the most important operational method.

Let f (t) = given function defined for all t 0.

Multiply f (t) by

st

e

and integrate with respect to t from 0 to . We have;

where:

F (s)

F (s)

f (t)

=

0

st

e

f (t)dt

= Laplace transform of the original function and will be denoted by L(f).

= original function

(1) F (s) = L(f) = 0 e f (t)dt

st

Remember that:

 f depends on t F depends on s

The original function f (t) in (1) is called the inverse transform or inverse of F (s) and will be

denoted by

1

L

(F). f (t) =

1

L

(F)

Notation:

Original functions are denoted by lowercase letters Transforms by the same letters in CAPITALS

So that:

F (s) denotes the transform of f (t)

Y (s)

denotes the transform of y(t)

Example 1.

f

(t)

= 1 when t 0. Find

F (s) .

From (1) by integration:

F (s) = L(f) =

0 e

st

f (t)dt

=

=

e

0

1

s

st

0

dt

st

e

(

s dt

)

1

1

1

2

=

=

dt

1

1

{ (

2

{ (

2

at

e

(

ans.

s a

1 (

Solution:

Solution:

Example 3:

Using the table:

 1 ) + 1 1 1 2 s + a 1 ) + − a 2 s 1 1 ( ( ) 2 a 1 + s + a + − − a a s s s ( [ ] 2 ( s − )( + a s a ) 1 2 s [ ] 2 ( − a s 2 2 ) s − a s 2 2 ans.

PROOF: By definition;

 − st [ ∞ = − e 0 s = − 1 { e s( − ∞ ) s = − 1 {0 − 1} s F (s) = L(1) = 1 s

Application of theorem 1:

L{af (t) + bg(t)} = aL{ f (t)} + bL{g(t)}

L{af (t) + bg(t)} = aL{ f (t)} + bL{g(t)}

THEOREM 1: Linearity of the transform

when t 0. Find F (s) where a is constant.

Example 2. Laplace Transform of the exponential function.

F (s) = L( e

at

) = 0 e

st

dt

e

at

=

+

0 e

dt

at

st

=

0

)

(

e

t

a

s

=

0

)

]

t

=

0

)0

(

)

]

[

a

s

a

s

e

e

dt

L

g t

e

b

t dt

f

e

a

bg t

t

af

st

st

( )

( )

( )}

( )

{

0

0

+

+ =

dt

L

)}

at

at

e

e

L

+

=

g t

b

t

af

e

bg t

t

af

st

( )]

{

( )

[

( )}

( )

{

0

+

+ =

)

(

2

1

)

L ( e

2

1

)}

at

at

at

at

L e

e

e

L

+

=

+

F (s) = L( e

at

) =

ans.

)

) =

(

at

e

t

f

+

. Find F (s) .

s

=

t

)

a

a dt

(

)

)(

F (s) = L(f) =

st

0 e

f (t)dt

a

s

=

=

=

f (t)

=

a

e

}

s(0)

e

s

a

1

1 [

0

1

e

e

(

s

(

s

a

s

1]

a

[0

s

a

Example 4:

 f (t) = a + bt + ct 2 Solution: L ( a + bt + ct 2 ) = = = Example 5: bt f Solution: ( ) = t − e a . Find F (s) .

aL

a

(1)

)

(

1

a

s

+

b

a,b,c = cons tan ts . Find F (s) .

+ bL t

(

( )

)

1

2

+ b

s

2! c

+

s

s

2

s

3

+ cL t

+ c

(

2

2!

s

(

3

)

)

ans.

(

L e

a

bt

)

=

=

L e e

1

( s

+

b

)

(

e a

a

bt

)

=

e L e

a

(

bt

)

e a

= s

+

b

ans.

Practice Problems:

1. Find the Laplace transforms of the following functions. Show the details of your work.

a. t 2 - 2t

b. (t 2 – 3) 2

c. cos 2πt

d. sin 4t

e. e 3a-2bt

TRANSFORMS OF DERIVATIVES:

Laplace transforms replaces operations of calculus by operations of algebra on transforms.

“ The differentiation of f (t) is replaced by multiplication of L(s) by s .”

 (1) L ( f ' ) ==== sL ( f ) −−−− f (0) ; f (t) is continuous for all t ≥≥≥≥ 0 where: L ( f ' ) = Laplace transform of the first derivative of f (t)

L( f )

= Laplace transform of f (t) ; also F (s)

f (0)

= value of the function at time t ==== 0

 And: L ( f L ( f L ( f Similarly; L ( f Or in general; L ( f

''

''

''

'''

n

)

)

)

)

)

==== sL ( f

'

)

==== s [ sL

==== s

2

L

(

(

f

f

)

 −−−− f ' (0) ; substitute L ( f ' ) in (1) ) −−−− f (0)] −−−− f ' (0)

−−−− sf

(0)

−−−− f

'

(0)

==== s

3

L

(

f

)

−−−− s

2

f

(0)

−−−− sf

'

(0)

−−−− f

''

(0)

====

s

n

L

(

f

)

−−−−

s

n

−−−−1

f

(0)

−−−−

s

n

−−−−2

f

'

(0)

−−−−

f

n

−−−−1

(0)

Example 1:

f (t)

Solution:

= t

2

. Derive L( f ) .

1. Take the derivatives

f (t)

= t

f (0) ==== 0

2

2

f (0) ==== 0

 f ' t ( ) = 2t f '' t ( ) = 2 f ' (0) ==== 2(0) f '' (0) ==== 2 f ' (0) ==== 0

2. Take the Laplace of the highest derivative of f (t) .

L

(

f

''

)

==== L

(2)

====

2

L

(1)

3. Substitute to equation of differentiation of the highest derivative

L

''

f

( )

==== s

2

L

(

L (2)

==== s

2

L

(

f

f

)

−−−− sf

(0)]

−−−− f

)

−−−− s

(0)]

−−−−

(0)

From the table

2

s

====

s

2

L

(

f

)

L (2) ====

'

(0)

2

s

L

(

f

)

====

2

s

3

ans. (see table)

Note: Different Process but same answer!!!

Example 2:

Derive the Laplace transform of cos wt .

Solution:

1. Differentiate f (t)

 f (t ) ==== cos wt ' f (t) ==== −−−− w sin wt f '' (t) ==== −−−− w f (0) ==== cos w(0) f ' (0) ==== −−−−w sin w (0) f '' (0) ==== −−−−w f (0) ==== 1 f ' (0) ==== 0 f '' (0) ==== −−−−w

2

2

2

cos wt

cos

w

(0)

2.

Take the Laplace of the highest derivative of f (t) .

L

L

(

(

f

f

''

''

)

)

==== L ( −−−−w

2

cos

wt

)

But: f (t) = cos wt

==== −−−−w

2

L

(cos

wt

)

==== −−−−w

;

2

L

(

f

)

w

2

====

constant

3. Substitute to equation of differentiation of the highest derivative

L

(

f

''

)

−−−− w

2

L

==== s

(

f

)

s ==== s

2

L

(

f

2

L

(

==== s

f

)

2

L

)

++++ w

2

−−−− sf

(0) −−−− f

(

f

L

(

)

f

−−−− s

)

(1) −−−−

L

L

(

f

)

(cos

====

s

s

2

++++

w

2

wt

)

====

s

s

2

++++

w

2

 ' (0) (0) ans. (see table)

Assignment:

1. Derive L(sin wt ) using transforms of derivative.

2.

f

(

t

) ==== sin

2 t

INITIAL VALUE PROBLEMS:

Given the Differential Equation:

(5)

where:

y

''

+ ay

'

+ by = r t

( )

a & b = constants r(t) = input (driving force) applied to the mechanical system y(t) = output (response of the system)

1 st Step: Transform (5) by means of (1) and (2) writing Y = L( y) & R = L(r)

''

y

[s

2

'

+ ay

Y sy(0)] y (0)] + a[sY y(0)] + bY = R

+ by =

( )

r t

'

this is the subsidiary equation

Collecting Y terms we have;

'

s Y sy(0) y (0) + asY ay(0) + bY = R

(s

2

2 + as + b)Y = (s + a) y(0) + y'(0) + R

2 nd Step: Solve the subsidiary equation algebraically for Y. Multiply the subsidiary equation by:

(6)

1

coeff

of

Y

= Q Transfer

(

_

function

(7)

[(

Y

1

s

2

+

as

+

b Y

)

]

(

2

+

as

+

b

)

=

[(

s

= [(s + a) y(0) + y'(0)]Q + RQ

If y(0) = y'(0) = 0

Y = RQ

Q ====

Y L( output

====

R L( input )

)

s

+

a

)

y

)

(0)

+

y

'(0)

+

R Q

]

Note that Q depends only on a & b, neither on r(t) or initial condition.

3 rd Step: Reduce (7) usually by partial fraction, to a sum of terms whose inverse can be found from the table so that;

Example 1:

( )

y t

=

L

1

(

Y

)

Solve: y"y = t

Solution:

of (5) is obtained.

;

y(0) = 1

;

y'(0) = 1

1. From the table and (2) get the subsidiary equation

2.

y"y = t

s 2

'

Y −−−− sy( 0 ) −−−− y ( 0 ) −−−− Y ====

1

s

2

1

2

s Y

=

=

=

 s (1) − (1) − Y = s 2 ( s 2 − 1) Y = s + 1 + 1 2 s 1 Q = s 2 − 1 1 ( s +1) Q + 2 Q s s + 1 1 + s 2 − 1 s 2 ( s 2 − 1) s + 1 1 1 + [ − ] ( s − 1)( s + 1) ( s 2 − 1) s 2

The transfer function is

Y

Y

Y

and (7) becomes;

Y =

1

1

1

(

s

1)

(

s

2

1)

s

2

+

3. From this expression, find y(t) from table.

y ( t )

=

( ) =

y t

L

e

t

1

(

Y

)

=

+ sinh

L

1

t

t

{

(

1

s

1)

}

+ L

1

{

1 }

1)

s

2

(

ans.

1

L

{

1

s

2

}

Diagram:

 Given Problem y"−y'= t y(0) = 1 y'(0) = 1 t space Solution of the Given Problem ( ) = y t e t + sinh t − t t space 1. y "+2 y '+ y = e − t y(0) = −1 2. y'+3y = 10sin t y(0) = 0 3. y'+0.2 y = 0.01t y(0) = −0.25 4. y"− y'−2 y = 0 y(0) = 8
Subsidiary
Equation
1
2
(
s −
1)
Y = s +
1
+
2
s

s space

 Solution of Subsidiary Equation 1 1 1 Y = + − ( s − 1) ( s 2 − 1) s 2

s space

y'(0) = 1

y'(0) = 7

Practice Problems:

LAPLACE TRANSFORM OF THE INTEGRAL OF A FUNCTION

Theorem:

“Integration of a function corresponds to division of its transform by s”

L

t

{

0

f

d

(τ) τ}

=

F

(

s

)

s

;

s > 0

Or if we take the inverse transform

 t ∫ 0 F ( s ) f d (τ) τ = L − 1 { s } where: t f t ( ) = ∫ 0 f d (τ) τ Example: L ( f ) = ( s s 2 1 + w 2 ) Solution:

Find f (t).

Note that:

From the table we have:

1
1
1
L
(
) =
sin wt
2
2
s
+ w
w
t
F
(
s
)
1
f
( t
)
=
f
(τ)
d
τ
=
L
{
}
0
s
1
1
= L
{
}
2
2
s s
(
+
w
)

From this and Theorem 3 we have:

f

( )

t

Note from table:

=

=

t

0

t

0

f

f

(τ)

(τ)

d

τ

d

τ

=

=

L

L

1

1

{

{

F

(

s

)

s

}

1

s ( s

2

+

w

2

)

}

L

1

(

1

s

2

+

2

w

Then;

) =

1

w

f (t)

sin wt

=

=

=

t

0

(

1

w

1

w

1

t

w

1

sin

w

τ

)

d

τ

[

0 sin w

d

τ τ

1

w

t

0

sin

w

τ

(

w d

)

τ

]

=

=

=

2

w

1

w

1

2

w

2

 [ ] t 0 − cos w τ [ − cos wt − ( − cos w (0))] [1 − cos wt ] ans.

Example 2: Derive the formula 20 in table using the transform of Integrals

Solution:

L

(

f

) =

1 Find f (t).

s

2

(

s

2

+

w

2

)

f (t)

=

t

0

f

(τ)

d

τ

=

From the table we have:

L

1

(

(

s s

2

1

+

w

2

)

)

=

1

2

w

[1

cos

wt

]

L

1

{

1

s

2

(

s

2

+

2

w

)

}

=

t

0

[

1

2

w

(1

cos

w

τ

)]

d

τ

 = = = = f (t) = Practice Problems: 1. 1 L − ( 5 1 3 ) s + s 2. 1 L − ( s 3 1 − s )

1

2

w

1

2

w

1

w

1

2

2

w

1

3

w

t

0

(1

[

τ

cos

sin w

w

τ

w

τ

]

t

0

)

d

τ

{[

t

0]

[

sin

wt

sin

w

(0)

w

w

]}

[ t

[

wt

sin wt

]

w

sin

wt

]

ans.